Issues in implementing CRM: a case study - da Silva, R.; Rahimi, I. (Issues in Informing Science and Information Technology, 2004)
In recent years several large organizations in Israel implemented CRM systems in order to increase efficiency. The difficulties managers and decision makers in all fields of business have to face are great as there is no one 'fixed formula' to guarantee the success of such a maneuver. However, there is a set of guidelines that can assure the road to success of such a change when one wishes to implement an ERP system. Holland and Light's (1999) CSF model that was designed to ensure successful ERP implementation is at the heart of the present paper. They present tactical and strategic processes to ease such a process. This paper shall focus on two of the following issues: First the paper will examine whether it is possible to extend the Holland and Light model and make it suitable to CRM implementation, and second, it will review the modifications that the model must undergo in order to achieve this objective. Twenty companies of various industrial fields that implemented CRM were reviewed. The paper presents the case study of three of these companies. The analysis of the interviews and survey that is currently being processed in Israel will be presented at the conference.